Preliminary feasibility of integrating tobacco treatment into SUD peer recovery coaching: a mixed-methods study of peer recovery coaches - Joanna M. Streck; Susan Regan; Michael Werner; Alexia Glynn; Andrea C. Villanti; Elyse R. Park; Sarah E. Wakeman; A. Eden Evins; Nancy A. Rigotti (Addiction Science & Clinical Practice, 2023)
Abstract Background Individuals with substance use disorder (SUD) have high prevalence of cigarette smoking and difficulty quitting. Peer recovery coaches (PRCs; individuals with lived SUD experience) facilitate SUD behavior change in recoverees but it is unknown if/how they address tobacco treatment in SUD recovery coaching. We assessed PRC’s tobacco-related practices and attitudes about tobacco treatment in SUD recovery. Methods The Tobacco use In Peer-recovery Study (TIPS) was a cross-sectional mixed-methods pilot survey (January–March 2022) of the 26 PRCs employed by a Massachusetts-based healthcare system’s 12 SUD treatment clinics/programs. PRCs completed a quantitative survey (n = 23/26; 88%) and a telephone-based qualitative interview (n = 20/26; 77%). Results One-third of PRCs reported current smoking, 50% reported former smoking, and 18% never smoked. Among PRCs, 61% reported accompanying recoverees outdoors to smoke, 26% smoked with recoverees, 17% had provided cigarettes to recoverees, 32% used smoking to help build peer-relationships, and 74% rated smoking as socially acceptable in SUD treatment. PRCs reported regularly talking to recoverees about tobacco treatment (65%), believed they should have a role in helping recoverees quit smoking (52%), and were interested in tobacco treatment training (65%). A majority of both nonsmoking and current smoking PRCs (73% vs. 57%) regularly talked to recoverees about quitting smoking. Conclusion PRCs’ attitudes about integrating tobacco treatment into SUD recovery coaching were generally positive and PRCs reported they could have a role in helping recoverees with tobacco treatment. Barriers to integrating tobacco treatment into SUD recovery include use of cigarettes as a peer-recovery tool and high prevalence and social acceptability of smoking in SUD recovery.